Evaluation of Crash Energy Management of the First-Developed High-Speed Train in Indonesia - Karisma Rizal; Achmad Syaifudin (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Crash energy management is an essential evaluation stage of passive safety systems for high-speed trains. As a part of crash energy management, crash energy absorption has been researched for the last decade. The development of its components has also been performed individually. This paper presents a numerical analysis of the configuration of an energy absorption system for high-speed trains developed in Indonesia. Three placement configurations of the energy absorption system were investigated using explicit dynamic analysis in ANSYS. Total energy absorption, deceleration pulse, and deformation length were considered in the evaluation of the numerical analysis results. The collision criteria used in this study were according to EN 15227 and CFR 238 standards. This study revealed that the existing design could fulfill the energy absorption and average deceleration pulse required by EN 15227. Nevertheless, the existing design could not fulfill the energy absorption and maximum deceleration pulse required by CFR 238. It was also indicated that by positioning the anti-climber slightly forward, changing the deformation force of the crush box, and adding an impactor, the quality of energy absorption and average deceleration pulse could be improved.